Association of NR4A1 and GNB2L1 genes with reproductive traits in commercial pig breeds - T. Kumchoo (2018)
© FUNPEC-RP. The nuclear receptor subfamily 4, group A, member 1 (NR4A1) and guanine nucleotide binding protein beta polypeptide 2 like-1 (GNB2L1) genes are expressed during the ovulatory process and in early pregnancy in pigs. The objective of this study was to analyze the effects of NR4A1 and GNB2L1 gene variants on reproductive traits in commercial pig breeds. Two single nucleotide polymorphisms (SNPs) of NR4A1 and GNB2L1 were identified by a polymerase chain reaction-restriction fragment length polymorphism method. Analysis of the association of these two SNPs with reproductive traits was evaluated in 515 commercial sows (273 Large White and 242 Landrace). The SNP NR4A1 g.3952A>G showed a significant association with the total number of piglets born, the number of piglets born alive, the number of piglets weaned alive, and the litter weight at weaning in the Landrace sows (P < 0.05). A significant association of SNP GNB2L1 g.2373T>C with the litter weight at birth was observed in the Large White sows (P < 0.05). These results indicate that the porcine NR4A1 and GNB2L1 can be used as candidate genes for improvement of litter size traits in pigs.